2019
DOI: 10.26630/jk.v10i2.1263
|View full text |Cite
|
Sign up to set email alerts
|

Efektifitas Pemanfaatan Media Gambar Bergerak dan Video Animasi terhadap Peningkatan Pengetahuan dan Sikap Ibu tentang Gizi Seimbang pada Balita

Abstract: <p><span>The fact that malnutrition occurs during the golden age is irreversible, so more attention is needed in the growth and development of toddler age.</span><strong> </strong><span data-preserver-spaces="true">This research is aim to find out the improvements of mothers’ knowledge concerning balanced nutrition for children under five before and after intervention by using moving picture and animated video media in Ambarawa public health center working area in Pringsewu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
3
0
8
Order By: Relevance
“…There is a change in knowledge and attitudes where respondents can see pictures that are alive and alternate so as to provide continuous visuals, with a combination of pieces of two or more images, helping to meet the need for images that are in accordance with learning objectives. (Febriani et al, 2019)illustrated pocket books are more concrete, that is, they can more realistically show the main problem compared to animation media so that they can see the problems conveyed in the message. When the respondent pays attention to the delivery of information that the researcher provides through a picture pocket book about the prevention of pulmonary TB transmission, there is a transfer of information that causes the cognitive knowledge of the respondent to be better than the animation media intervention.…”
Section: B Test Results Paired Sample T-testmentioning
confidence: 99%
“…There is a change in knowledge and attitudes where respondents can see pictures that are alive and alternate so as to provide continuous visuals, with a combination of pieces of two or more images, helping to meet the need for images that are in accordance with learning objectives. (Febriani et al, 2019)illustrated pocket books are more concrete, that is, they can more realistically show the main problem compared to animation media so that they can see the problems conveyed in the message. When the respondent pays attention to the delivery of information that the researcher provides through a picture pocket book about the prevention of pulmonary TB transmission, there is a transfer of information that causes the cognitive knowledge of the respondent to be better than the animation media intervention.…”
Section: B Test Results Paired Sample T-testmentioning
confidence: 99%
“…18,23 Other research made videos only and showed significant results regarding mothers' knowledge and attitudes; however, their effects were not calculated. 24,25 The demonstration in videos with non-animated roleplaying (by humans) shows the complete sensing process accompanied by roleplaying, which gives better results than lectures and videos only. 21 The combination of animation and nonanimation, as in this research, can further activate the five senses to gain effective results.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous research suggested that animation can still provide significant changes. 24,25 Early breastfeeding initiation is crucial 27 -education on keeping babies warm shows a medium effect. However, the medium effect is still good, and if the videos were to be watched again, they could still increase knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Sejalan dengan penelitian Hartati et al, (2019) didapatkan bahwa Ada pengaruh yang signifikan video animasi terhadap tingkat pengetahuan dan sikap remaja putri pada kelompok perlakuan dan kelompok kontrol. Sejalan pula dengan penelitian yang dilakukan oleh Febriani et al, (2019) terdapat perbedaan signifikan pengetahuan dan sikap ibu tentang gizi seimbang pada balita antara dua kelompok (media animasi dan media gambar bergerak). media tersebut disebabkan informasi tentang gizi melalui media animasi secara langsung menyebabkan yang menyebabkan kognitif pengetahuan responden pun lebih baik dibandingkan pada intervensi media gambar bergerak Ibu lebih mudah dalam memahami apa yang disampaikan, proses pengajaran lebih menarik, ibu akan dirangsang untuk aktif mengamati tanpa adanya penjelasan secara rinci karena hanya menggunakan indra penglihatan.…”
Section: Pembahasanunclassified